Sociocultural Analysis of Stigma and Humour in Psychiatry - Greš, Alen; Staver, Dijana; Radovančević, Ljubomir; Šakić, Branislav (Scripta Medica, 2025)
In psychology and psychiatry, humour has long been used as a therapeutic tool, a coping strategy and a technique for societal criticism. Although laughter is considered a sign of health, it is paradoxically often used in the context of mental illness, creating space for both healing and stigma. This paper explores a sociocultural and psychoanalytic analysis of humour directed at psychiatrists. Examines how it may be a stigmatising factor as well as a therapeutic ally. The main contribution lies in articulating how humour functions as a projective tool, a defence mechanism and a cultural critique. It highlights the prejudices, often overlooked fears and biases society has about mental illness and psychiatry. The analysis demonstrates that humour is not insignificant in the field of psychiatry. On the contrary, it is essential for understanding social representations of mental health, the patient-doctor dynamic and the emotional landscape of stigma. The paper concludes by suggesting directions for future empirical research. Both qualitative and quantitative research should explore how different humour styles - adaptive or maladaptive impact therapy, reduce stigma and build resilience in both patients and clinicians.